ДОСЛІДЖЕННЯ ТЕРМОГАЗОДИНАМІКИ ПАЛЬНИКА ЗІ ЗМЕНШЕНОЮ ГЕНЕРАЦІЄЮ ОКСИДІВ АЗОТУ ДЛЯ ПИЛОВУГІЛЬНОГО КОТЛА ТПП 312 - Kobzar, S.G (Institute of Engineering Thermophysics of NAS of Ukraine, 2024)
The paper was consider the influence of the flue gas recirculation in inner duct of coal dust burner. The concept of a burner with reduced generation of nitrogen oxides for the TPP 312 boiler was created. It was used the principle of prolonging combustion process by separating the high-temperature zone from free oxygen by flue gas. The obtained results are shown that the proposed concept of the burner allows reduce nitrogen oxides up to 15%. The maximum reduction of nitrogen oxides was observed at 10% recirculation of flue gases/